PENGARUH PUPUK HAYATI DENGAN KOMPOSISI MIKROORGANISME YANG BERBEDA TERHADAP PERTUMBUHAN TANAMAN - Amalia Puji` Cahyani; Asri Pirade Paserang; Meryany Ananda; Wahyu Harso (Biocelebes, 2021)
Biofertilizer can be used to replace chemical fertilizer so that soil quality is maintained and soil pollution can be avoided. The study aimed to determine the effect of biofertilizers with different compositions of microorganisms on the growth of maize plants. The research was carried out in a greenhouse. Maize plants were fertilized by two kinds of biofertilizers with different compositions of microorganisms. The first biofertilizer contained Azotobacter sp, Azospirillum sp, Rhizobium sp, Trichoderma sp, and Lactobacillus sp, and the second biofertilizer contained Strenotrophomonas sp. and Paenibacillus polymyxa. As controls, maize plants were fertilized by sterilized those biofertilizers. The results showed that the second biofertilizer increased the dry weight of the maize plant. Meanwhile, the first biofertilizer did not increase it. Several things must be considered in the application of biofertilizers, such as the composition of microorganisms, type of plant, level of fertilization, and the method of applying fertilizer to the plant.